2022
DOI: 10.3390/biology11101501
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Signatures of Auditory False Perception and Phantom Perception as a Consequence of Sensory Prediction Errors

Abstract: In this study, we hypothesized that top-down sensory prediction error due to peripheral hearing loss might influence sensorimotor integration using the efference copy (EC) signals as functional connections between auditory and motor brain areas. Using neurophysiological methods, we demonstrated that the auditory responses to self-generated sound were not suppressed in a group of patients with tinnitus accompanied by significant hearing impairment and in a schizophrenia group. However, the response was attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…In the study conducted by Ahn and colleagues [ 3 ], the function of top-down sensory prediction error and efference copy (EC) signals to investigate the effects of peripheral hearing loss on auditory false perception and phantom perception is examined. Patients in the study have either schizophrenia or tinnitus accompanied by varied degrees of hearing loss.…”
mentioning
confidence: 99%
“…In the study conducted by Ahn and colleagues [ 3 ], the function of top-down sensory prediction error and efference copy (EC) signals to investigate the effects of peripheral hearing loss on auditory false perception and phantom perception is examined. Patients in the study have either schizophrenia or tinnitus accompanied by varied degrees of hearing loss.…”
mentioning
confidence: 99%
“…These findings give rise to a few pertinent questions. What all within the framework of predictive processing using EEG and talk-listen paradigm (Ahn et al, 2022). Lack of N100 suppression was observed in both, tinnitus patients with severe (but not mild) hearing loss and patients with psychosis but not in tinnitus without hearing loss, suggesting a common dysfunction in predictive processing following severe sensory deprivation in tinnitus and psychotic hallucinations.…”
Section: Outlook and Parting Thoughtsmentioning
confidence: 92%
“…Participants produced vowels and then listened to their own voice recordings (i.e., 'Talk/Listen' paradigm) while EEG was recorded. The results indicated that N100 suppression, which is typically indicative of successful sensory processing, was reduced in schizophrenia patients and in the group of tinnitus with hearing difficulties (which also showed increased levels of hearing loss when compared to the tinnitus group without hearing difficulties) (Ahn et al, 2022). The authors thus argued that hearing loss and self-perceived hearing impairment may influence N100 suppression to selfgenerated sounds (Ahn et al, 2022).…”
Section: Tinnitus In the Context Of Hallucinatory Experiencesmentioning
confidence: 99%
“…In humans, position predictions were investigated in tinnitus and results indicated increased variability in the amount of suppression a person with tinnitus displays (Ahn et al, 2022;Campbell, Bean, & LaBrec, 2018). In animals, on the other hand, where evoked potentials in the MGB were analyzed, results indicated successful gating of formal-, temporal-, and position predictions (Zare et al, 2023).…”
Section: Brain Correlates Of (Auditory) Predictionmentioning
confidence: 99%
See 1 more Smart Citation